2006
DOI: 10.3892/ijmm.18.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Comano's (Trentino) thermal water interferes with the expression and secretion of vascular endothelial growth factor-A protein isoforms by cultured human psoriatic keratinocytes: A potential mechanism of its anti-psoriatic action

Abstract: Abstract. Thermal balneotherapy with Comano spa's water (CW; Trentino, Italy) is used for psoriasis and other skin disorders but the mechanism(s) of action of this hypotonic water are unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
(74 reference statements)
1
24
0
Order By: Relevance
“…Here, we will show that the addition of CW (in total or partial stead of DW) to the growth medium remarkably hinders the hyper-expression of TNF-· and the heightened production and release of IL-8 on the part of the psoriatic keratinocytes. Therefore, our previous (49,50) and present findings are consistent with CW being endowed with a complex phenotype-and cytokine/chemokine-regulating potential that translates into valuable anti-psoriatic therapeutic benefits.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…Here, we will show that the addition of CW (in total or partial stead of DW) to the growth medium remarkably hinders the hyper-expression of TNF-· and the heightened production and release of IL-8 on the part of the psoriatic keratinocytes. Therefore, our previous (49,50) and present findings are consistent with CW being endowed with a complex phenotype-and cytokine/chemokine-regulating potential that translates into valuable anti-psoriatic therapeutic benefits.…”
Section: Introductionsupporting
confidence: 73%
“…In conclusion, our previous (49,50) and present observations support the view that CW balneotherapy may elicit its beneficial effects by interfering with an improper local production and secretion of several chemokines and cytokines, including TNF-·, IL-8, IL-6, and various VEGF-A isoforms, and by attenuating some facets, such as CK-16 expression, of the psoriatic phenotype, which altogether locally underlie the epidermal hyperplasia and dermal neoangiogenesis, inflammation, and leukocyte infiltration phenomena proper of psoriatic illness.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Actually, some studies have shown that Comano thermal water is able to reduce the expression of some cytokines (TNF-α, IL-6 and IL-8) involved in the inflammatory process, relating this property to its anti-psoriatic efficacy in humans (15,16). Unlike corticosteroid action, such a specific effect against the inflammatory reaction does not counteract cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the mechanisms through which the clinical signs of psoriasis (and of the other above mentioned skin disorders) are improved by means of CW balneotherapy have not as yet been clarified. In a previous study, we showed that exposure to CW interferes with VEGF-A isoform expression and secretion by the human psoriatic keratinocytes (54). To further clarify the mechanism(s) possibly involved in the therapeutic effectiveness of CW balneotherapy in psoriasis, we investigated CW's effects on IL-6 hyper-production and hyper-secretion and on CK-16 expression by epidermal keratinocytes isolated from lesional skin biopsies.…”
Section: Introductionmentioning
confidence: 99%